Anti-Osteoporosis Potencies of Zingiber officinale Rosc. Rhizome Water Extract and DFA III Produced from Dahlia spp. L.: in vivo and in vitro Studies - Muthi’ Ikawati; Yogi Ertanto; Een Sri Endah; Sri Pudjiraharti; Edy Meiyanto; Riris Istighfari Jenie (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Zingiber officinale Rosc. is estrogenic and thus can be developed as an anti-osteoporosis. Difructose anhydride III (DFA III), possesses anti-osteoporosis potencies. This study aimed to investigate the anti-osteoporosis activity of ginger rhizome water extract (GE) and DFA III from dahlia tubers in ovariectomized (OVX) rat models and to determine their anti-osteoclastogenic effect in vitro.METHODS: This study was conducted using 25 female rats. Blood sampling was carried out at the beginning and end of treatments. Femur bones were isolated after daily 14-day treatments, measured for density, and processed for histological staining. RAW 264.7 cells were induced by osteoclast differentiation factor. A cell viability assay was employed to determine the cytotoxicity of DFA III and GE. The inhibition of osteoclastogenesis was investigated by tartrate-resistant acid phosphatase staining.RESULTS: All groups showed no difference in body weight elevation and serum lipid profiles. The GE and DFA III caused no effect on bone density. However, the GE or DFA III groups showed higher osteoblast numbers compared with the control groups. A significantly less osteoclast was found in the GE+DFA III group. The GE and DFA III showed no toxicity on RAW 264.7 cells. GE showed strong inhibitory effects on the post stimulation osteoclastogenesis model. The combination of GE and DFA III was synergistic in reducing the osteoclastogenesis confluency in RAW 264.7 cells.CONCLUSION: The data support our hypothesis that GE and DFA III can decrease the risk of osteoporosis by osteoclastogenesis inhibition.KEYWORDS: Dahlia spp., estrogenic, ginger, osteoclast, osteoporosis, ovariectomy, RAW 264.7 cell